The Influence of Perceived Personalization on Sustainable Purchase Decision: The Mediating Roles of AI Trust and Customer Experience - Wiena Aprilia; Arvin Said; Raysha Fadillah Raihany; Nurul Asrillah; Zahra Aulia; Dwi Martiyanti (FEB Universitas Mulawarman, 2025)
Increasing competition in the beauty industry requires companies to continuously innovate and improve service quality. One rapidly growing innovation is the application of personalized artificial intelligence (AI) services to provide experiences relevant to individual needs and build customer trust in the brand. This study aims to analyze the perceived influence of personalization on the AI Skin Analyzer feature on purchasing decisions by examining the mediating role of customer experience and trust in AI. This study uses a quantitative approach involving 150 respondents who are beauty website users who have used the AI Skin Analyzer feature in Samarinda. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationship between variables. The results show that perceived personalization significantly influences customer purchasing behavior. This relationship was also mediated by experience and trust in the AI skin analyzer. The study shows that the use of personalized AI leads to positive experiences, increases trust, and has a positive impact on purchasing behavior. These findings contribute to the understanding of how personalized AI services can shape consumer perceptions and behaviors in the beauty industry